1998
DOI: 10.1242/dev.125.9.1711
|View full text |Cite
|
Sign up to set email alerts
|

Discrete spatial and temporal cis-acting elements regulate transcription of the Arabidopsis floral homeotic gene APETALA3

Abstract: The APETALA3 floral homeotic gene is required for petal and stamen development in Arabidopsis. APETALA3 transcripts are first detected in a meristematic region that will give rise to the petal and stamen primordia, and expression is maintained in this region during subsequent development of these organs. To dissect how the APETALA3 gene is expressed in this spatially and temporally restricted domain, various APETALA3 promoter fragments were fused to the uidA reporter gene encoding beta-glucuronidase and assaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The molecular mechanism we discovered here is consistent with most published data on AP3 and PI regulation (Chae et al, 2008; Hill et al, 1998; Honma and Goto, 2000; Tilly et al, 1998). However, precise understanding of regulation of AP3 and RBE will require further work on other cis and trans -elements.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The molecular mechanism we discovered here is consistent with most published data on AP3 and PI regulation (Chae et al, 2008; Hill et al, 1998; Honma and Goto, 2000; Tilly et al, 1998). However, precise understanding of regulation of AP3 and RBE will require further work on other cis and trans -elements.…”
Section: Discussionsupporting
confidence: 91%
“…To decipher the molecular mechanism underlying the synergistic action of LFY and UFO, we used a Dual Luciferase Reporter Assay (DLRA) to analyze their ability to activate promoters when transiently expressed in Arabidopsis protoplasts. We found that pAP3, the best characterized LFY-UFO target (Hill et al, 1998; Lamb et al, 2002), is strongly activated when LFY (or LFY-VP16, a fusion of LFY with the VP16 activation domain; Parcy et al, 1998) is co-expressed with UFO (or UFO-VP16) but not by either effector alone (Figure 1A and 1E). We also tested the promoter of RABBIT EARS ( RBE ), a gene expressed in petal primordia in a UFO-dependent manner (Krizek et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A series of ORFs, including IiAP3 , IiPI and chimeras of IiAP3 and IiPI , were prepared by PCR or overlapping PCR, and were inserted into the binary expression vectors pCAMBIA 1302 possessing a GFP gene controlled by CaMV 35S promoter (Benfey & Chua, 1990), and pRI 101‐AN containing CaMV 35S promoter or 5D2 promoter, to drive a constitutive or tissue‐specific expression, respectively, of the transgenes in wild‐type Arabidopsis plants or ap3‐6 and pi‐1 mutants. The 1036 bp 5D2 promoter of AtAP3 was used as a tissue‐specific regulatory sequence in petals and stamens (Hill et al, 1998). The final constructs were verified by restriction digestion, PCR and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%